2015
DOI: 10.1586/14789450.2015.1056782
|View full text |Cite
|
Sign up to set email alerts
|

From global proteome profiling to single targeted molecules of follicular fluid and oocyte: contribution to embryo development and IVF outcome

Abstract: The development of in vitro fertilization (IVF) techniques for infertility management has led to the investigation of the proteome of follicular fluid and oocyte. In addition, different markers contributing to oocyte maturation and embryo development potential have been reported in the literature. Different techniques were utilized to analyze whole proteome or single protein markers in follicular fluid and oocytes, particularly in animal models. Data from several studies have generated large amounts of informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 158 publications
1
19
0
Order By: Relevance
“…In the postgenomic era, proteomic techniques have been widely used in the field of reproductive medicine. HFF proteome has become a hotspot for research, which not only contributed to discovering proteins related to IVF outcomes, but also improved our comprehensive understanding of physiological process during follicle development and oocyte maturation [ 11 ]. Li and co-workers used surface-enhanced laser desorption/ionization-time of flight-mass spectrometry (SELDI-TOF-MS) combined with weak cation-exchange protein chip (WCX-2) to search for differentially expressed HFF proteins from mature and antral follicles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the postgenomic era, proteomic techniques have been widely used in the field of reproductive medicine. HFF proteome has become a hotspot for research, which not only contributed to discovering proteins related to IVF outcomes, but also improved our comprehensive understanding of physiological process during follicle development and oocyte maturation [ 11 ]. Li and co-workers used surface-enhanced laser desorption/ionization-time of flight-mass spectrometry (SELDI-TOF-MS) combined with weak cation-exchange protein chip (WCX-2) to search for differentially expressed HFF proteins from mature and antral follicles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human follicular fluid (HFF) provides a special and ideal microenvironment for oocyte maturation, composed of steroid hormones, metabolites and proteins, which are required for follicle development and oocyte maturation [7][8][9]. Importantly, HFF can be easily obtained during the aspiration of oocytes from follicle in the procedure of in vitro fertilization (IVF), which facilitates it to be as a useful source for the biomarker screening for oocyte maturation [10]. Proteomic technology has been applied to explore key molecules for the better understanding of the physiological processes involved in follicle development and oocyte maturation.…”
Section: Open Accessmentioning
confidence: 99%
“…Proteins being translated from RNA are directly responsible for cellular function, but different gene expression studies have, unfortunately, shown that a reliable prediction of proteins' function or abundance cannot be made. As for the human proteome, significant advances have been made for the analysis of the whole proteome and of the proteome of different disease states [3,5,[10][11][12][13][14][15][16][17][18][19][20]. Bearing all of it in mind, the analysis of proteins obtained from the cultivating media is challenging, and the results are not always conclusive.…”
Section: Albumin Depletion In Ivf Cultivation Mediummentioning
confidence: 99%